Enhancing Student Character: A Bibliometric Study on The Role of Local Wisdom Approaches - Abdul Salam; Agus Setiawan; Aminuddin Prahatama Putra; Yadi Ruyadi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The present research aims to analyze the development, trends, and intellectual structure of research on the role of local wisdom approaches in character building among students through a bibliometric study. Method: Bibliometric analysis using Scopus-indexed publication data for the 2014–2024 period. Data were obtained through a search using the keywords